My Future Is in America : Autobiographies of Eastern European Jewish Immigrants. - Cohen, Jocelyn (NYU Press, 2005)
In 1942, YIVO held a contest for the best autobiography by a Jewish immigrant on the theme "Why I Left the Old Country and What I Have Accomplished in America." Chosen from over two hundred entries, and translated from Yiddish, the nine life stories in My Future Is in America provide a compelling portrait of American Jewish life in the immigrant generation at the turn of the twentieth century. The writers arrived in America in every decade from the 1890s to the 1920s. They include manual workers, shopkeepers, housewives, communal activists, and professionals who came from all parts of Eastern.